222k views
3 votes
Factor 6x? + x – 12 by grouping.
C

1 Answer

4 votes

Answer:

6x² + x - 12 = (2x + 3) (3x - 4)

Explanation:

Factor 6x² + x - 12 by grouping

we need to rewrite the middle term as a sum of two terms whose product is (6* −12) = −72 and whose sum is 1

The middle term = x = 9x - 8x

6x² + x - 12

= 6x² + 9x - 8x - 12 Grouping the first two terms and the last two terms

= (6x² + 9x) + ( - 8x - 12)

From the first two terms take 3x as a common and from the two terms take (-4) as a common

= 3x ( 2x + 3) -4 (2x + 3)

Take (2x + 3) as a common

= (2x + 3) (3x - 4)

User Victoria Seniuk
by
6.5k points